Islamic Law in Indonesia (History and Prospects) - Wahyuni, Sri (Batulis Civil Law Review, 2023)
This article discusses about Islamic Law in Indonesia in history perspective. This article analyses the problem and prospect of Islamic law in Indonesia as epistemologically discourse. This article asays that the Islamic law of Indonesia has developed since Dutch East Indies Period. It mixed in the customary law of Indonesian muslim people. Indonesia in the post colonial period, which uses Eropha Contnental Legal System makes a legislation to establish the national law. Therefore, Islamic law may become the national law if it’s drafted as a bill to be enacted, such as marriage law (act of 1, 1974 on marriage), law No. 10 of 1998 on the amendment of Law No. 7 of 1992 on Banking, the law no. 35, 1999 on Zakat Management, the law no. 17, 1999 on hajj, and the law no. 3, 2006 on the Amandment of the law no. 7, 1989 on eligion Court.